HOMOGENIZATION OF TWIN-ROLL CAST Al-Li-BASED ALLOY STUDIED BY IN-SITU ELECTRON MICROSCOPY - CIESLAR, Miroslav; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko (METAL 2022 Conference Proeedings)
Transformation of Fe- and Cu-rich primary phase particles was studied in an Al-Li-based alloy prepared by twin-roll casting. Thin foils for combined STEM and SEM experiments were prepared by electrolytic twin-jet polishing. They were in-situ heated in a TEM heating stage and observed at 200 kV in the JEOL JEM 2200FS electron microscope equipped with STEM HAADF and BF detectors and SEM BSE and SE detectors working both in composition and topographic modes. The resulting structures were combined with EDS mapping performed directly in the heating holder. Dissolution and transformation of Cu- and Fe-rich particles occur above 500 °C. EDS maps acquired on the foil cooled down to room temperature show that Cu and Fe are both still present in newly formed particles, most likely indicating the presence of the Al7Cu2Fe phase.
Keywords: Al-Li-based alloy; in-situ TEM; homogenization; phase transformation